2001
DOI: 10.1111/j.1527-3466.2001.tb00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Properties of Yangambin, a Lignan Isolated from Brazilian Plants

Abstract: Yangambin was initially selected from a number of lignans isolated from Brazilian plants for its ability to antagonize Platelet-Activating Factor (PAF, 1-O-hexadecyl-2-acetyl-sn-glyceryl-3-phosphorylcholine)-induced biological effects. Subsequently it was shown that, besides its antagonistic properties at PAF receptors, yangambin also prevents the cardiovascular collapse observed during anaphylactic and endotoxic /septic shocks, as well as the vascular and cardiac hyporesponsiveness to catecholamines in endoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 70 publications
0
10
0
3
Order By: Relevance
“…Plant lignans have been reported to exert anti-PAF activity (Biftu & Stevenson, 1987;Shen & Hussaini, 1990;Tibirica, 2001). Flaxseed potentially inhibits several mechanisms associated with renal disease in lupus nephritis.…”
Section: Hepatoprotective Effectsmentioning
confidence: 99%
“…Plant lignans have been reported to exert anti-PAF activity (Biftu & Stevenson, 1987;Shen & Hussaini, 1990;Tibirica, 2001). Flaxseed potentially inhibits several mechanisms associated with renal disease in lupus nephritis.…”
Section: Hepatoprotective Effectsmentioning
confidence: 99%
“…Studies have revealed that it is a specific PAF inhibitor which antagonizes competitively PAF binding to its receptor [22]. It displays beneficial actions against allergy and headache [23, 24] along with its cardioprotective role [25]. …”
Section: Organic Paf Inhibitorsmentioning
confidence: 99%
“…Phytochemical and biological studies have identified potential antitumoural substances including some lignans [10]. These substances may display a variety of pharmacological properties including immunosuppressive [11], vasoactive [12], antioxidant [13], antiviral [14], anti-inflammatory [15] and antitumoural [16] actions. Lignans are an important class of secondary metabolites found in many plant species belonging to more than seventy families [17].…”
Section: Introductionmentioning
confidence: 99%